Management of Children With β-Thalassemia Intermedia: Overview, Recent Advances, and Treatment Challenges. Issue 4 (May 2018) - Adly, Amira A.; Ismail, Eman A.
Abstract : Our knowledge of the various clinical morbidities that thalassemia intermedia (TI) patients endure has substantially increased over the past decade. It is mandatory to grasp a solid understanding of disease-specific complications in order to tailor management. The optimal course of management for TI patients has been hard to identify, and several controversies remain with regard to the best treatment plan. Although advances in TI are moving at a fast pace, many complications remain with no treatment guidelines. Studies that expand our understanding of the mechanisms and risk factors, as well as clinical trials evaluating the roles of available treatments, will help establish management guidelines that improve patient care. Novel therapeutic modalities are now emerging. This article focuses on the management of children with β-TI. We present various clinical morbidities and their association with the underlying disease pathophysiology and risk factors. All therapeutic options, recent advances, and treatment challenges were reviewed.